Hydrological regimes in a tropical valley of New Caledonia (SW Pacific): Impacts of wildfires and invasive fauna. Issue 3 (8th March 2021) - Tramier, Caroline Marie Clémence; Genthon, Pierre; Delvienne, Quentin Réginald Camille Paul; Sauvan, Nicolas Luc; Cassan, Jean‐Jérôme Olivier; Ebrard, Etienne; Dumas, Pascal Sébastien; Queffélean, Yann
Abstract: In New Caledonia wildfires and invasive mammals (deer and wild pigs) constitute the major agents of land surface degradation. Our study reveals the linkage between land cover and water balance on the northeast coast of New Caledonia (2400 mm annual rainfall) located on a micaschist basement. The hydrological regime of characteristic and representative land surfaces is assessed using a 1‐year record from three 100 m 2 plots each, located in a forest area degraded by an invasive fauna, in a woody savannah which is regularly burned, and in a healthy forest area. The three plots present highly contrasting hydrological regimes, with annual and maximum runoff/rain ratios during a rain event of, respectively, 0.82, 0.16, 0.03, and 2.7, 0.7, 0.2, for the degraded forest, the savannah and the healthy forest. Such results suggest that subsurface flow originating from the contributing area above the degraded forest plot should exfiltrate inside the plot. A conceptual model for the degraded forest plot shows that water exfiltrating inside the plot represents 61% of the observed runoff. In savannahs, water should mainly be transferred downstream by subsurface flow within a thick organic soil layer limited by an impervious clay layer at a 20–30 cm depth. Savannahs are generally located above forests and generate the transfer of rainwater to downslope forests. Exfiltration into the forests can be the result of this transfer and depends on the thickness and permeability of the forest topsoils and on topographic gradients. Water exfiltration in forest areas highly degraded by pigs and deer enhances erosion and increases further degradation. It probably also limits percolation in the areas located downstream by increasing the amount of superficial runoff concentrated in gullies. Abstract : Striking differences in runoff properties are found in experimental plots located in characteristic land surfaces in the North East New Caledonia. Annual runoff coefficients are in the range of 0.28–0.82 for a forest degraded by invasive mammals (deer and wild pigs), 0.06–0.16 for a woody savannah, and 0.01–0.03 for a healthy forest. It is proposed that arrangement of these three land surfaces in the landscape may control runoff properties at the scale of a watershed.